A New Compound Heterozygous Mutation Of BSCL2 In A Chinese Zhuang Ethnic Family With Congenital Generalized Lipodystrophy - Qin Y (Dove Medical Press, 2019)
Yuan-yuan Qin,1 Xuan Zhang,1 Li-qun Xiang,1 Qing-wen Shan,2 Shou-dong Li,3 Jie Yan,1 Fa-quan Lin1 1Department of Clinical Laboratory, The First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region, People’s Republic of China; 2Department of Pediatric, The First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region, People’s Republic of China; 3Guangxi Anren Xin Bio Technology Co., Ltd, Nanning, Guangxi Zhuang Autonomous Region, People’s Republic of ChinaCorrespondence: Fa-quan LinThe First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region, People’s Republic of ChinaTel +86-771-5329287Email fqlin1998@163.comPurpose: This study aims to report the clinical features of an infant with CGL in a Chinese Zhuang ethnic family, whose family members were discovered to carry new pathogenic mutations in the BSCL2.Patients and methods: In this study, we report clinical and molecular investigations of CGL disease in a family of 4 members (parents and two sons). We used whole exome sequencing (WES) in the family to examine the genetic cause of the disease.Results: The proband presented with skin pigmentation, hypertriglyceridemia and diabetes. WES identified a previously unreported compound heterozygous mutation in the BSCL2 (c.545_546insCCG heterozygous mutation and exon 3 heterozygous deletion) in the proband. His mother is a heterozygous carrier of the c.545_546insCCG mutation and his father and brother are carriers of the exon 3 heterozygous deletion.Conclusion: Compound heterozygous mutation of the BSCL2 (new c.545_546insCCG heterozygous mutation and new exon 3 heterozygous deletion) was detected in the proband with characteristic clinical manifestations of CGL2.Keywords: congenital generalized lipodystrophy, pigmentation, hypertriglyceridemia, diabetes, BSCL2 mutation, whole exome sequencing